Sports Counseling Preparation at CACREP Institutions: An initial Analysis - Wooten, Jr., H. Ray; Miller, Gary (My University, 2001)
Interest in the field of sports counseling is growing in both mental health and athletics communities. Specialized sports counseling preparation has been emphasized in order to work efficiently with athletes. However; it is not clear whether counseling programs have the curriculum, faculty, or departmental support for those interested in becoming sports counselors. This survey of 63 counseling programs accredited by the Council for Accreditation of Counseling and other Related Educational Programs (CACREP) examined the availability of training opportunities for counseling students interested in specialization in sports counseling and the attitudes of the counseling faculty toward sports counseling. Findings reveal a lack of training opportunities in sports counseling at CACREP accredited institutions and only moderate interest by faculty in establishing such programs.
Keywords: CACREP; counseling; academic support; curriculum